The Relationship between Language Anxiety and Willingness to Communicate in English Speaking Classes among EFL Vocational Students - Adinda Safitri; Nita Kaniadewi (Universitas Islam Negeri Palopo, 2026)
Vocational EFL learners face distinct communicative demands because their curriculum emphasizes workplace-oriented English use. However, many students still hesitate to participate in English speaking activities due to psychological barriers. Drawing on the Foreign Language Anxiety (FLA) framework and MacIntyre et al. (1998) Willingness to Communicate (WTC) model, this study examined the relationship between these two constructs among Grade 10 students at a vocational high school in Jakarta, Indonesia. A quantitative correlational research design was employed involving 107 students from the Digital Business, Retail Business, and Office Management programs. Data were collected using the adapted Foreign Language Classroom Anxiety Scale (FLCAS) and the Willingness to Communicate Scale (WTCS). Both instruments demonstrated satisfactory validity and reliability, with Cronbach's Alpha coefficients of 0.757 and 0.913, respectively. Because the assumption of linearity was not satisfied, the relationship between the variables was analyzed using Spearman's Rank-Order Correlation. The analysis revealed a statistically significant negative correlation between Foreign Language Anxiety and Willingness to Communicate (ρ = −0.201, p = 0.038), The relatively weak correlation suggests that Foreign Language Anxiety is one of several factors associated with students' willingness to communicate, alongside other psychological, contextual, and instructional influences. Although the relationship was relatively weak, the findings confirm that Foreign Language Anxiety remains an important affective factor associated with vocational students' willingness to communicate. This study extends understanding of the relationship between Foreign Language Anxiety and Willingness to Communicate in the underexplored Indonesian vocational EFL context and offers practical implications for creating supportive, low-anxiety classroom environments that foster students' communicative confidence and active participation in English speaking activities.